APPLICATION OF CONSOLIDATED DEPLOYMENT PC SEAT BCA PROJECT MANAGEMENT USING MS-VISUAL BASIC 6.0 - Nayusman Bakri N; Yulina SKom, MMSI Yulina SKom, MMSI (Jurnal Sistem Informasi, 2006)
This application aims to accelerate the preparation of reports BCA Deployment PCSeat Management Project, which has been implemented by the deployment team withthe help of the media PC computer through a Visual Basic 6.0. Therefore expectedthat the Project Manager can easily evaluate the performance of your pc and thedeployment team can make the right decisions for the achievement of employmenttargets that had been predetermined.